ธรรมชาติของวิชาเคมี และการจัดการเรียนการสอนให้สอดคล้องกับ ธรรมชาติของวิชา Nature of Chemistry and Performing an Instruction to be Consistent with Its Nature - ร่มพยอม วิชัยดิษฐ, พัชรี (Science Essence Journal, 2015)
บทคัดย่อ ผู้เรียนส่วนใหญ่มักประสบปัญหาในการเรียนวิชาเคมี และเห็นว่าเนื้อหาวิชาเคมีนั้นเข้าใจยาก นักการศึกษาด้านวิทยาศาสตร์ได้อธิบายสาเหตุหลักของความยากของวิชาเคมีว่า เนื้อหาวิชาเคมีมีความเป็นนามธรรม ผู้เรียนมีอุปสรรคเกี่ยวกับภาษาสัญลักษณ์ที่ใช้ในการเรียนการสอน และการจัดการเรียนการสอนของครูมักจะขัดแย้งกับธรรมชาติการเรียนรู้ของผู้เรียน ทั้งนี้นักการศึกษาด้านวิทยาศาสตร์ได้อธิบายธรรมชาติของวิชาเคมีว่า แนวคิดทางเคมีจำแนกเป็น แนวคิดในระดับมหภาค ระดับอนุภาค และภาษาสัญลักษณ์ ดังนั้น ในการจัดการเรียนการสอนวิชาเคมี ครูผู้สอนต้องจัดให้สอดคล้องกับธรรมชาติของวิชาเคมี และธรรมชาติของการเรียนรู้ของผู้เรียน การเรียนวิชาเคมีจึงจะไม่ใช่สิ่งที่ยากเกินไปสำหรับผู้เรียน คำสำคัญ: การนำเสนอแนวคิดทางเคมี 3 ระดับ ธรรมชาติของวิชาเคมี การนำเสนอแนวคิดระดับมหภาค การนำเสนอแนวคิดระดับอนุภาค การนำเสนอแนวคิดที่เป็นภาษาสัญลักษณ์ ทฤษฏีการเรียนรู้ Abstract Most students often face with difficulty in learning chemistry and perceive that the chemistry content is difficult to understand. Science educators describe the main causes of the difficulty of learning chemistry. For example, the chemistry content is abstract, the students have difficulties with symbolic language used in teaching, and chemistry teaching is often performed in the way that distorted with the nature of student learning. Moreover, the science educators explain the nature of chemistry that chemical knowledge can be explained in three different levels: macroscopic level, microscopic level and symbolic level. Therefore, during the instruction, the teacher needs to be consistent with the nature of chemistry and also the nature of student learning. By doing so, learning chemistry is not too difficult to learn and chemistry may not be a tough subject. Keywords: Multiple representations in chemistry, Nature of chemistry, Macroscopic representation, Microscopic representation, Symbolic representation, Learning theory